Collaboration between traditional healers and psychiatrists in Sudan - Sorketti, E.A.; Zuraida, N.Z.; Habil, M.H. (Royal College of Psychiatrists UK, 2010)
The importance of traditional healing in low- and middle-income countries cannot be underestimated. It is generally perceived as part of the prevailing belief system and traditional healers are often seen as the primary agents for psychosocial problems in these countries; estimates of their service share range from 45% to 60% (World Health Organization, 1992).The World Health Organization (2000) estimated that 80% of people living in rural areas in low- and middleincome countries depend on traditional medicine for their health needs.In Sudan, a country with a mixed Arab/African culture,traditional healing is the most common method of treating people with mental illness, mostly because it is usually far cheaper than medical treatment (Elsafi & Baasher, 1981–94) but also because of the inaccessibility of medical services and lack of awareness among the population.